2012
DOI: 10.1016/j.foodchem.2011.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Possible causes of variation in acrylamide concentration in French fries prepared in food service establishments: An observational study

Abstract: Acrylamide is a probable human carcinogen, and its presence in a range of fried and oven-cooked foods has raised considerable health concern world-wide. Dietary intake studies observed significant variations in acrylamide concentrations, which complicate risk assessment and the establishment of effective control measures. The objective of this study was to obtain an insight into the actual variation in acrylamide concentrations in French fries prepared under typical conditions in a food service establishment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 37 publications
6
35
0
Order By: Relevance
“…In a previous study, it was shown that these FSEs represent the common types of FSE (besides small restaurants) and they use similar types of frying equipment (Sanny et al, 2012). The CFS and IC types use fryers that are equipped with a temperature controller and a timer.…”
Section: Characteristics Of Food Service Establishmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, it was shown that these FSEs represent the common types of FSE (besides small restaurants) and they use similar types of frying equipment (Sanny et al, 2012). The CFS and IC types use fryers that are equipped with a temperature controller and a timer.…”
Section: Characteristics Of Food Service Establishmentsmentioning
confidence: 99%
“…Sanny et al (2010) concluded in a qualitative study about FSE practices that inconsistent frying conditions, variation in initial concentration of reducing sugars, and food handler's inadequate control of these factors in their daily practice could lead to the observed large variation and high acrylamide concentrations in French fries. In another study in FSE, they found that the contribution of reducing sugars to the prediction of acrylamide formation in French fries prepared under the typical conditions of different types of FSE could not be confirmed (Sanny, Jinap, Bakker, van Boekel, & Luning, 2012). It was discussed that the effect of variable frying temperature and to a lesser extent, frying time, possibly overshadowed the effect of reducing sugars on acrylamide concentration.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The amount of acrylamide in food depends on processing conditions, such as temperature, time, nature of the food matrix, oil or microwave use [14,15]. Mojska et al [18] found the highest content of acrylamide in French fries (63-2175 μg/kg) and in potato chips (113-3647 μg/kg) [18].…”
Section: Introductionmentioning
confidence: 99%